2017
DOI: 10.1051/0004-6361/201731562
|View full text |Cite
|
Sign up to set email alerts
|

B stars seen at high resolution by XMM-Newton

Abstract: We report on the properties of 11 early B stars observed with gratings on board XMM-Newton and Chandra, thereby doubling the number of B stars analysed at high resolution. The spectra typically appear soft, with temperatures of 0.2-0.6 keV, and moderately bright (log[L X /L BOL ] ∼ −7) with lower values for later type stars. In line with previous studies, we also find an absence of circumstellar absorption, negligible line broadening, no line shift, and formation radii in the range 2 -7 R ⋆ . From the X-ray br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Further evidence for a direct connection between the photospheric conditions and the X-ray emission comes from the detection of X-ray pulsations in (at least) two stars of the class of β Cep pulsators: ξ 1 CMa [100] and β CMa [12]. These X-ray pulsations (at the ∼ 10% level, see Fig.…”
Section: Earthmentioning
confidence: 95%
See 1 more Smart Citation
“…Further evidence for a direct connection between the photospheric conditions and the X-ray emission comes from the detection of X-ray pulsations in (at least) two stars of the class of β Cep pulsators: ξ 1 CMa [100] and β CMa [12]. These X-ray pulsations (at the ∼ 10% level, see Fig.…”
Section: Earthmentioning
confidence: 95%
“…The top panel illustrates the Hipparcos photometry, retaining only points with uncertainties of less than 0.005 mag, folded with the 6.03 h pulsation period [150]. The bottom panel illustrates the EPIC count rate from XMM-Newton revolution 2814 folded with the same period and zero point [12].…”
Section: Earthmentioning
confidence: 99%
“…However, as all LDI models thus far have been computed for stars with mass-loss rates well above 10 −8 M /yr, it remains to be investigated how LDIgenerated shocks develop in the weak-wind regime. Indeed, although previous LDI models have been successful in explaining X-ray emission from dense O-supergiants (Feldmeier et al 1997), X-ray observations of late O-type stars (Huenemoerder et al 2012;Doyle et al 2017) and early B-type stars (Cazorla & Nazé 2017) do seem to indicate that these winds might have larger portions of hot gas embedded in them.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer investigations have sought to frame massive stars in terms of an X-ray classification based on high-resolution spectral data. Certainly, there have been efforts to group highresolution data in relation to stellar winds (Oskinova et al 2006;Waldron & Cassinelli 2007;Cazorla & Nazé 2017), magnetic stars (Oskinova et al 2011b;Nazé et al 2014;, or studies of individual colliding-wind binaries, such as η Carinae, WR 147, WR 140, WR 48a, and WR 25 (Corcoran et al 2001;Pollock et al 2005;Zhekov & Park 2010;Zhekov et al 2014;Pradhan et al 2021). Walborn et al (2009) explored trends for massive stars based on Chandra grating spectra and found a trend of X-ray hardness correlated with spectral subtype in O and early-B stars, indicating a correlation between X-ray plasma temperature and stellar effective temperature.…”
Section: Introductionmentioning
confidence: 99%